MFOA-integrated modified inverted F-based adaptive array Antenna for 2.4 GHz band applications - Supakit Kawdungta; Chuwong Phongcharoenpanich (My University, 2016)
This research has proposed a modified fruit fly optimization algorithm (MFOA)-integrated adaptive array antenna (AAA) for the 2.4–2.5 GHz WLAN system. The principal components of the array antenna system encompass four array elements, four band pass filters (BPF), four digital phase shifters, a four-way power combiner/splitter, a directional coupler, a radio frequency (RF) detector, and a microcontroller unit (MCU). In the realization of the adaptive antenna system, the modified inverted F antenna with a finite ground plane was first innovated and subsequently deployed as the element of the four-element array antenna. In the study, simulations and experiments were carried out with the four-element AAAs of two configurations, i.e. the linear and planar array configurations. The simulation and experimental results revealed that the MFOA algorithmic scheme could determine the direction of the maximum arrival signal in an efficient and accurate manner and also was capable of manipulating the radiation pattern in the desired direction. In addition, the MFOA-integrated four-element AAA is of compact size (20 mm × 35 mm × 1.8 mm) and operable in the 2.31–2.55 GHz frequency band with omnidirectional radiation pattern and a gain of 1.6 dBi. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2016.
Keywords: Passive radiator; Antenna Design and Optimization